STABILITY AND IRRITATION TESTING USING THE PATCH TEST METHOD OF A COMBINATION GEL FORMULATION CONTAINING ALOE VERA AND BASIL LEAF EXTRACTS - Yasir, Angga Saputra; Suryaneta, Suryaneta; Handayani, Kiki Yuli; Satria, Bagus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Aloe vera and basil leaves have been recognized for their anti-inflammatory and antibacterial properties. Combining these extracts into a gel formulation offers convenience in application. However, research concerning potential irritations associated with its use remains limited. This study aims to assess irritation in humans resulting from the application of a gel formulation containing basil and aloe vera extracts using patch testing. The gel formulation is prepared with a 2% concentration of the extracts, with a 1:1 ratio of basil to aloe vera extracts. Optimization is achieved by varying carbopol concentrations and the final pH of the gel formulation. The parameters used for determining the optimal formula include organoleptic characteristics, viscosity, spreadability, adhesiveness, and pH of the formulation. The optimal formula is subsequently subjected to stability testing over four weeks and irritation testing using patch methods. A total of 25 volunteers are involved in the irritation testing. Observations are made up to 72 hours after the removal of the formulation to ensure the absence of delayed irritation effects. Aloe vera and basil extractions using ethanol as a solvent yield sequential yields of 1.7% and 3%, respectively. Quality evaluation for Formulations I (FI), II (FII), and III (FIII) includes spreadability, adhesiveness, and viscosity, as follows: (4.1 cm; 5.4 seconds; 5504 mPa.s); (6.5 cm; 4.1 seconds; 3480 mPa.s); and (5.2 cm; 4.2 seconds; 6340 mPa.s), respectively. FII is selected as the optimal formula because it exhibits wider spreadability and lower viscosity compared to FI and FIII (P <0.05). Stability testing for FII shows that the formula remains stable during storage for all quality testing parameters (P > 0.05). The Primary Irritation Index (PII) for FII has a value of 0.0216, indicating that it does not cause irritation during patch testing.